Applying a Consumer Behavior Lens to Salt Reduction Initiatives - Áine Regan (Nutrients, 2017)
Reformulation of food products to reduce salt content has been a central strategy for achieving population level salt reduction. In this paper, we reflect on current reformulation strategies and consider how consumer behavior determines the ultimate success of these strategies. We consider the merits of adopting a ‘health by stealth’, silent approach to reformulation compared to implementing a communications strategy which draws on labeling initiatives in tandem with reformulation efforts. We end this paper by calling for a multi-actor approach which utilizes co-design, participatory tools to facilitate the involvement of all stakeholders, including, and especially, consumers, in making decisions around how best to achieve population-level salt reduction.